MICROBIOME OF THE EYE SURFACE IN INFECTIOUS KERATOCONJUNCTIVITIS IN CATTLE: COMPARATIVE ANALYSIS BY STAGE OF LESION - B. Abdigulov; B. Yessimov; T. Karibaiev; G. Nigmatulla; A. Shevtsov (Animal Health and Biosafety, 2026)
Infectious bovine keratoconjunctivitis (IBK) remains one of the most significant ophthalmological pathologies in cattle. Culture-based methods make it possible to isolate key pathogens; however, they do not reflect the complete structure of the microbial community of the affected ocular surface. In this pilot study, amplicon sequencing of the V3–V4 regions of the 16S rRNA gene was performed using conjunctival smears from 15 calves with IBK; a total of 30 samples were analyzed, with each eye considered as a separate analytical unit. The microbiome was compared between lesion stages 3, 4, and 5 (10, 10, and 8 samples, respectively). Bioinformatic processing was performed in QIIME 2 v2025.7 using DADA2 and the GreenGenes2 taxonomic database. After filtration, 873 bacterial ASVs were identified. The community was dominated by Moraxella, Mycoplasma, Pasteurellaceae, Streptococcus, and Mannheimia-associated taxa. The median values of Faith’s PD decreased as the severity of the lesion increased (Kruskal–Wallis test, p = 0.015), while the Shannon index showed no statistically significant differences (p = 0.371). Weighted UniFrac analysis revealed a moderate but statistically significant structural shift between stages 3 and 5 (PERMANOVA, q = 0.021). These findings suggest that disease progression may be accompanied not only by changes in the abundance of individual bacterial taxa, but also by broader alterations in the phylogenetic composition of the conjunctival microbiome. In this context, 16S rRNA amplicon sequencing may serve as a useful complementary approach to culture-based diagnostics, especially for characterizing polymicrobial patterns associated with severe ocular lesions. Taking into account the pilot design, the absence of a healthy control group, and the animal–eye pair structure, the results should be considered as the basis for further studies with expanded sampling and functional validation.